Answer:
Meaning
Step-by-step explanation:
<em>The value of b is 14 and the value of c is 65</em>
<h2>
Explanation:</h2>
The quadratic function is a function of the form:
![f(x)=ax^2+bx+c](https://tex.z-dn.net/?f=f%28x%29%3Dax%5E2%2Bbx%2Bc)
Here we know that the leading coefficient
so we reduce our equation to:
![g(x)=x^2+bx+c](https://tex.z-dn.net/?f=g%28x%29%3Dx%5E2%2Bbx%2Bc)
The roots are those values at which ![g(x)=0](https://tex.z-dn.net/?f=g%28x%29%3D0)
So:
![x^2+bx+c=0 \\ \\ First \ root: \\ \\ (-7+4i)^2+b(-7+4i)+c=0 \\ \\ (-7)^2-2(7)(4i)+(4i)^2-7b+4bi+c=0 \\ \\ 49-56i+16i^2-7b+4bi+c=0 \\ \\ \\ Simplifying: \\ \\ 49-56i+16(-1)-7b+4bi+c=0 \\ \\ 49-56i-16-7b+4bi+c=0 \\ \\ 33-56i-7b+4bi+c=0 \\ \\ \\](https://tex.z-dn.net/?f=x%5E2%2Bbx%2Bc%3D0%20%5C%5C%20%5C%5C%20First%20%5C%20root%3A%20%5C%5C%20%5C%5C%20%28-7%2B4i%29%5E2%2Bb%28-7%2B4i%29%2Bc%3D0%20%5C%5C%20%5C%5C%20%28-7%29%5E2-2%287%29%284i%29%2B%284i%29%5E2-7b%2B4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%2049-56i%2B16i%5E2-7b%2B4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%5C%5C%20Simplifying%3A%20%5C%5C%20%5C%5C%2049-56i%2B16%28-1%29-7b%2B4bi%2Bc%3D0%20%5C%5C%20%5C%5C%2049-56i-16-7b%2B4bi%2Bc%3D0%20%5C%5C%20%5C%5C%2033-56i-7b%2B4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%5C%5C)
![Second \ root: \\ \\ (-7-4i)^2+b(-7-4i)+c=0 \\ \\ (-1)^2(7+4i)^2+b(-7-4i)+c=0 \\ \\ (7)^2+2(7)(4i)+(4i)^2-7b-4bi+c=0 \\ \\ 49+56i+16i^2-7b-4bi+c=0 \\ \\ \\ Simplifying: \\ \\ 49+56i+16(-1)-7b-4bi+c=0 \\ \\ 49+56i-16-7b-4bi+c=0 \\ \\ 33+56i-7b-4bi+c=0](https://tex.z-dn.net/?f=Second%20%5C%20root%3A%20%5C%5C%20%5C%5C%20%28-7-4i%29%5E2%2Bb%28-7-4i%29%2Bc%3D0%20%5C%5C%20%5C%5C%20%28-1%29%5E2%287%2B4i%29%5E2%2Bb%28-7-4i%29%2Bc%3D0%20%5C%5C%20%5C%5C%20%287%29%5E2%2B2%287%29%284i%29%2B%284i%29%5E2-7b-4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%2049%2B56i%2B16i%5E2-7b-4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%5C%5C%20Simplifying%3A%20%5C%5C%20%5C%5C%2049%2B56i%2B16%28-1%29-7b-4bi%2Bc%3D0%20%5C%5C%20%5C%5C%2049%2B56i-16-7b-4bi%2Bc%3D0%20%5C%5C%20%5C%5C%2033%2B56i-7b-4bi%2Bc%3D0)
So we have:
![(1) \ 33-56i-7b+4bi+c=0 \\ \\ (2) \ 33+56i-7b-4bi+c=0 \\ \\ \\ Subtract \ 2 \ from: \\ \\ 33-56i-7b+4bi+c-(33+56i-7b-4bi+c)=0 \\ \\ 33-56i-7b+4bi+c-33-56i+7b+4bi-c=0 \\ \\ \\ Combine \ like \ terms: \\ \\ 33-33-56i-56i-7b+7b+4bi+4bi+c-c=0 \\ \\ -112i+8bi=0 \\ \\ Isolating \ b: \\ \\ b=\frac{112i}{8i} \\ \\ \boxed{b=14}](https://tex.z-dn.net/?f=%281%29%20%5C%2033-56i-7b%2B4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%282%29%20%5C%2033%2B56i-7b-4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%5C%5C%20Subtract%20%5C%202%20%5C%20from%3A%20%5C%5C%20%5C%5C%2033-56i-7b%2B4bi%2Bc-%2833%2B56i-7b-4bi%2Bc%29%3D0%20%5C%5C%20%5C%5C%2033-56i-7b%2B4bi%2Bc-33-56i%2B7b%2B4bi-c%3D0%20%5C%5C%20%5C%5C%20%5C%5C%20Combine%20%5C%20like%20%5C%20terms%3A%20%5C%5C%20%5C%5C%2033-33-56i-56i-7b%2B7b%2B4bi%2B4bi%2Bc-c%3D0%20%5C%5C%20%5C%5C%20-112i%2B8bi%3D0%20%5C%5C%20%5C%5C%20Isolating%20%5C%20b%3A%20%5C%5C%20%5C%5C%20b%3D%5Cfrac%7B112i%7D%7B8i%7D%20%5C%5C%20%5C%5C%20%5Cboxed%7Bb%3D14%7D)
Finding c from (1):
![33-56i-7b+4bi+c=0 \\ \\ \\ Substituting \ b: \\ \\ 33-56i-7(14)+4(14)i+c=0 \\ \\ 33-56i-98+56i+c=0 \\ \\ -65+c=0 \\ \\ \boxed{c=65}](https://tex.z-dn.net/?f=33-56i-7b%2B4bi%2Bc%3D0%20%5C%5C%20%5C%5C%20%5C%5C%20Substituting%20%5C%20b%3A%20%5C%5C%20%5C%5C%2033-56i-7%2814%29%2B4%2814%29i%2Bc%3D0%20%5C%5C%20%5C%5C%2033-56i-98%2B56i%2Bc%3D0%20%5C%5C%20%5C%5C%20-65%2Bc%3D0%20%5C%5C%20%5C%5C%20%5Cboxed%7Bc%3D65%7D)
<h2>Learn more:</h2>
Complex conjugate: brainly.com/question/2137496
#LearnWithBrainly
Sorry but I’m just commenting because apparently you have to answer other people’s questions in order to ask questions even when you have Brainley plus ugh
Answer: area= 3846.5 inch^2
Step-by-step explanation:
Area of circle = πr^2
Where r is the radius and pi is 3.14
So, we get..
3.14 x (35)^2
= 3.14 x 35 x 35
= 3.14 x 1225
= 3846.5 inch^ 2